Mycoplasma genitalium: test positivity in syndromic presentations and clinicians' adherence with treatment guidelines at Sydney Sexual Health Centre. (October 2021) - Cheung, Calvin; Bourne, Christopher; Varma, Rick
Mycoplasma genitalium ( M.genitalium ) is associated with urethritis, cervicitis, pelvic inflammatory disease, proctitis and epididymitis. Its treatment is complicated by antimicrobial resistance. To assess clinicians' adherence to M.genitalium diagnostic testing recommendations for syndromic presentations, as well as resistance-guided management of M.genitalium at Sydney Sexual Health Centre, we reviewed patients presenting between August and December 2018. 349/372 (94%) syndromic presentations were tested for M.genitalium with 16% M.genitalium test positivity and 81% macrolide resistance. 16/27 (59%) macrolide-sensitive infections and 65/77 (84%) macrolide-resistant infections received resistance-guided treatment. Tests of cure (TOCs) were unnecessarily ordered for 82% macrolide-sensitive cases, while 88% macrolide-resistant cases were correctly ordered TOCs. Co-existing STIs at the time of macrolide-sensitive ( p = 0.30) or macrolide-resistant M.genitalium ( p = 0.94) diagnosis did not significantly affect adherence to treatment guidelines. This study confirms the expected prevalence of M.genitalium and macrolide resistance in syndromic presentations while our real-world data highlight the decision-making challenges involved with managing M.genitalium, offering insights for further research.